General Characteristics of Adjuvants and Their Mechanism of Action (Part 1) - N. A. Alpatova; Zh. I. Avdeeva; S. L. Lysikova; O. V. Golovinskaya; L. A. Gayderova (Биопрепараты: Профилактика, диагностика, лечение)
One of priority issues of the present-day healthcare system is development of new vaccines and improvement of existing ones due to decreasing immunocompetence of the population, emergence of new infections and reemergence of old ones which were previously thought to be under control. Adjuvants have proven to be integral and important components of modern vaccines, as they enhance immune response to the vaccine antigen. However, despite a lot of effort put into their development, only a small number of adjuvants are currently used in clinical practice. The aim of the study was to systematise literature data on the adjuvants’ mechanisms of action, their specific structure, composition, and stimulation effects that mediate their immunoadjuvant properties. The paper summarises data on adjuvants used as components in licensed vaccines, describes their characteristics, analyses molecular mechanisms of their action in order to establish correlation between their structure and activity, which is important for the development of more efficacious and safe adjuvants. The paper cites advanced developments aimed at enhancing stimulation effects of existing adjuvants. It concludes by stating that the key research area aimed at improving vaccination efficacy is the study of mechanisms that contribute to the development of effective protection against infectious agents, as well as analysis of how to use adjuvants to stimulate the body’s defensive mechanisms, primarily by impacting the innate immunity.